Contributions of mRNA abundance, ribosome loading, and post- or peri-translational effects to temporal repression of C. elegans heterochronic miRNA targets - Stadler, Michael; Artiles, Karen; Pak, Julia; Fire, Andrew (Genome Research, 2012)
miRNAs are post-transcriptional regulators of gene activity that reduce protein accumulation from target mRNAs. Elucidating precise molecular effects that animal miRNAs have on target transcripts has proven complex, with varied evidence indicating that miRNA regulation may produce different molecular outcomes in different species, systems, and/or physiological conditions. Here we use high-throughput ribosome profiling to analyze detailed translational parameters for five well-studied targets of miRNAs that regulate C. elegans developmental timing. For two targets of the miRNA lin-4 (lin-14 and lin-28), functional down-regulation was associated with decreases in both overall mRNA abundance and ribosome loading; however, these changes were of substantially smaller magnitude than corresponding changes observed in protein abundance. For three functional targets of the let-7 miRNA family for which down-regulation is critical in temporal progression of the animal (daf-12, hbl-1, and lin-41), we observed only modest changes in mRNA abundance and ribosome loading. lin-41 provides a striking example in that populations of ribosome-protected fragments from this gene remained essentially unchanged during the L3–L4 time interval when lin-41 activity is substantially down-regulated by let-7. Spectra of ribosomal positions were also examined for the five lin-4 and let-7 target mRNAs as a function of developmental time, with no indication of miRNA-induced ribosomal drop-off or significant pauses in translation. These data are consistent with models in which physiological regulation by this set of C. elegans miRNAs derives from combinatorial effects including suppressed recruitment/activation of translational machinery, compromised stability of target messages, and post- or peri-translational effects on lifetimes of polypeptide products.
10.1101/gr.136515.111